COMPRESSION OF THE TECHNOLOGICAL DATA IN TERMS OF GALOIS BASIC FUNCTIONS - Yatskiv, Nataliya (International Journal of Computing, 2014)
In this article data compression method on the basis of Galois basic functions of zero and first rank is proposed, efficiency of coding with the usage of this method is investigated.